METHODOLOGY («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The purpose of this article is to familiarize the participants of the conference with the most famous methodological directions, systems and methods, forms and means, as well as the latest technologies of teaching foreign languages in domestic and foreign methodology.
Keywords: Methodology and sociology, Methodology and general didactics, Methodology and logic, Methodology and informatics.